2021
DOI: 10.1037/emo0000681
|View full text |Cite
|
Sign up to set email alerts
|

Affective calculus: The construction of affect through information integration over time.

Abstract: Humans receive a constant stream of input that potentially influence their affective experience. Despite intensive research on affect, it is still largely unknown how various sources of information are integrated into the single, unified affective features that accompany consciousness. Here, we aimed to investigate how a stream of evocative input we receive is dynamically represented in self-reported affect. In 4 experiments, participants viewed a number of sequentially presented images and reported their mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 47 publications
9
42
0
1
Order By: Relevance
“…Several aspects need to be considered when interpreting the present results. The evaluation of affect in terms of valence and arousal may fluctuate from moment to moment and depend on the previously encoded material (Asutay et al, 2019), as well as on whether the stimulus is novel (i.e. seen for the first time) or familiar (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects need to be considered when interpreting the present results. The evaluation of affect in terms of valence and arousal may fluctuate from moment to moment and depend on the previously encoded material (Asutay et al, 2019), as well as on whether the stimulus is novel (i.e. seen for the first time) or familiar (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These contextual influences suggest that risky decision-making is fundamentally dynamic and temporally dependent on the impact of previous events. Affect, reflecting the individual's ongoing relationship with its surroundings, represents the cumulative impact of previous events [14,15]. Hence, it is a critical mechanism through which recent events influence subsequent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is a dynamic and temporally dependent mental process. Previous research has shown that momentary affective experience is shaped by a temporal integration of the currently active information and previously experienced affect [15,16]. Furthermore, it has been shown that moment-tomoment happiness ratings during risky decision-making depends on the prediction error history [17].…”
Section: Introductionmentioning
confidence: 99%
“…We found that self-reported current arousal indeed varied between good and bad symbols, however, it did not predict subsequent choices. As self-reported arousal ratings might be unreliable, it might be useful to simultaneously assess physiological arousal measures to enhance predictive power (Asutay et al, 2019). Future studies should further examine these findings and include physiological measures of autonomous activity instead of selfreported arousal in their choice prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…Studying how these changes in experimental design affect subsequent gambling decisions could elucidate how current and expected affect work together and which is causal for decisions. Moreover, we would like to point out that self-reported arousal might not be the best way to measure an emotional arousal component as it produces inconsistent results (Asutay et al, 2019). It might be better to additionally use physiological arousal measures.…”
Section: Discussionmentioning
confidence: 99%